Implementation of Radio Frequency Identification in Student Presence Applications with Multi Social Media Notification - Nishom, M.; Wibowo, Dega Surono; Bakti, Very Kurnia; Rais, Rais (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Radio-Frequency Identification or commonly called RFID is a technology that can be integrated into various softwares to increase operational efficiency and effectiveness. In an educational unit, one of the services that needs to be repaired or improved is recording student attendance. However, recording and monitoring student attendance in almost all educational units in Indonesia, and especially in Tegal City is still carried out conventionally, so that educational units cannot provide feedback to parents about their children's attendance in real time. This condition is the main basis for conducting this research. In this research, RFID technology was implemented into an desktop based application with the aim of making it easier for educational units to record student attendance automatically, and assisting schools in providing feedback about student attendance to parents through social media services (whatsapp or telegram) and increasing enthusiasm students in taking attendance. The method chosen for development is the waterfall method, this method ensures that all stages are carried out sequentially. The research application has been tested using the black box testing method, the test results indicate that the application functionality is running well.